Preparation method of mullite fiber reinforced spinel nanorod aerogel

Through hydrothermal synthesis and mullite fiber reinforcement methods, spinel nanorod aerogels with stable nanoframework and high mechanical properties were prepared, solving the problems of poor sintering, fusion and mechanical strength of existing aerogels at high temperatures.

CN119633700APending Publication Date: 2025-03-18AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411829910.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing aerogel materials are prone to sintering and fusing at high temperatures, resulting in collapse of nanoframes and thermal insulation failure. At the same time, their mechanical strength is poor, brittle and instability are difficult to mechanically shape dimensionally.

Method used

The spinel nanorod aerogel is prepared by hydrothermal synthesis method using magnesium oxide, alumina nanoparticles and inorganic acids, and a three-dimensional interpenetrating network structure is formed to improve the mechanical strength through the reinforcement of mullite fibers.

Benefits of technology

实现了尖晶石纳米棒气凝胶的纳米骨架稳定性和力学性能的提升,避免了烧结、融合和隔热失效的问题,同时降低了生产成本和工艺复杂性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633700A_ABST
    Figure CN119633700A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aerogel, and relates to a preparation method of mullite fiber reinforced spinel nanorod aerogel. The method comprises the following steps: adding aluminum oxide nanoparticles, magnesium oxide nanoparticles and inorganic acid into deionized water, and uniformly stirring and mixing at room temperature to obtain a weakly acidic dispersion liquid; adding a certain amount of mullite chopped fibers into the weakly acidic dispersion liquid, carrying out homogeneous dispersion to obtain a uniform and stable mullite fiber dispersion liquid, and carrying out high-temperature and high-pressure hydrothermal reaction on the uniform and stable mullite fiber dispersion liquid to obtain aqueous mullite fiber doped wet gel; placing the water-based mullite fiber doped wet gel in a low-surface-tension mixed solvent for solvent exchange to obtain low-surface-energy solvent-based mullite fiber doped wet gel, and drying and sintering the low-surface-energy solvent-based mullite fiber doped wet gel to obtain the mullite fiber doped spinel nanorod aerogel. The spinel nanorod aerogel disclosed by the invention has a thick and strong nano-skeleton, and the problems of collapse, volume shrinkage and heat insulation failure of the nano-skeleton of the aerogel are effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogels, and in particular to a method for preparing a mullite fiber reinforced spinel nanorod aerogel. Background Art

[0002] Aerogel has great application prospects due to its excellent characteristics such as low density, low thermal conductivity, high porosity, high thermal stability, and high specific surface area. It is widely used in functional catalysis, sensing, adsorption filtration, and thermal insulation. At present, the aerogel nano-skeleton prepared by the sol-gel process is slender and has extremely high surface energy. At temperatures far below the melting point of the material, sintering and fusion will occur between the nanoparticles, causing the nano-skeleton to collapse and the thermal insulation to fail. On the other hand, pure aerogel has ultra-low density and high porosity, resulting in poor mechanical strength, brittleness, and instability, making it difficult to mechanically shape, and therefore cannot be used alone.

[0003] In response to the above problems, researchers at home and abroad have carried out a lot of research work. In terms of improving the performance of aerogel materials, researchers use doping, compounding and other methods to prepare binary and multi-component composite aerogels, and limit the sintering of nanoparticles by inhibiting physical mass transfer to improve the temperature resistance of the material. Patent CN202410102806.5 discloses a high-temperature resistant magnesium aluminum spinel aerogel and a preparation method thereof. Basic magnesium sulfate whiskers and aluminum sol are used as the main raw materials, and a high-temperature resistant magnesium aluminum spinel aerogel is prepared by a freeze-drying method. However, the pore size (5-30μm) of the aerogel prepared by this method is much larger than the nanopore structure (1-100nm) of conventional aerogels, which will significantly aggravate the gas phase heat conduction and thermal convection of the thermal insulation material. The freeze-drying method is costly, the process is complicated and the cycle is long, making it difficult to achieve continuous production.

[0004] Patent CN201711059943.1 discloses a method for preparing a fiber-reinforced high-temperature resistant magnesium-aluminum spinel aerogel. After magnesium source, aluminum source, epoxide catalyst, etc. are used to prepare magnesium-aluminum binary sol, the fiber is immersed in the magnesium-aluminum sol, and the fiber-reinforced magnesium-aluminum spinel aerogel is obtained after gelation, aging, drying, and heat treatment. However, the basic unit of the aerogel prepared by this method is a nanoparticle, which is very easy to sinter and fuse during high-temperature heat treatment, resulting in the collapse of the aerogel nano-skeleton, which is macroscopically manifested as volume shrinkage; in addition, in terms of improving the mechanical properties of aerogel materials, using fiber felt blocks as a matrix will lead to an increase in the overall density of aerogel composite materials, which increases the solid-phase heat conduction of aerogels, and the overall thermal insulation performance of the material will be greatly reduced. Therefore, it is an urgent issue to develop an aerogel material that is both high-temperature resistant, lightweight, low thermal conductivity, high strength, and low cost. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a mullite fiber reinforced spinel nanorod aerogel, the method comprising the following steps:

[0006] Step 1: adding aluminum oxide nanoparticles, magnesium oxide nanoparticles and inorganic acid into deionized water in a certain proportion, stirring and mixing at room temperature to obtain a weakly acidic dispersion;

[0007] Step 2: adding a certain amount of mullite chopped fibers into the weakly acidic dispersion to homogenize and disperse the fibers to obtain a uniform and stable mullite fiber dispersion;

[0008] Step 3: subjecting the mullite fiber dispersion to a high temperature and high pressure hydrothermal reaction to prepare a water-based mullite fiber-doped wet gel;

[0009] Step 4: placing the water-based mullite fiber-doped wet gel in a mixed solvent with low surface tension for solvent exchange to obtain a low surface energy solvent-based mullite fiber-doped wet gel;

[0010] Step 5: drying the low surface energy solvent-based mullite fiber-doped wet gel to obtain the mullite fiber-doped aerogel, and then sintering the gel to obtain the mullite fiber-doped spinel nanorod aerogel.

[0011] Preferably, the average particle size of the aluminum oxide nanoparticles in the first step is 8-30 nm; the average particle size of the magnesium oxide nanoparticles is 5-25 nm; the inorganic acid is any one of hydrochloric acid, sulfuric acid, and nitric acid, or a mixture of several of them; the mass ratio of aluminum oxide nanoparticles: magnesium oxide nanoparticles: inorganic acid: deionized water in a certain proportion is 1:1:(0.3-0.5):(20-30); the pH value of the weakly acidic dispersion is 3-5.

[0012] Preferably, in the second step, the continuous mullite loose wool is sheared into mullite chopped fibers, and the continuous mullite loose wool is mullite nanofibers with a diameter of 100-500nm; the mullite chopped fibers are sheared by a fully automatic fiber cutting machine, and the length of the chopped fibers is 50-500μm; a high-speed disperser is used for the homogeneous dispersion, and the conditions for the high-speed disperser to perform the homogeneous dispersion are: a rotation speed of 3000-8000rpm, and a dispersion time of 15-40min; the concentration of the mullite fiber dispersion is 3-8wt%.

[0013] Preferably, in the third step, the mullite fiber dispersion is placed in a hydrothermal kettle for high-temperature and high-pressure hydrothermal reaction, the reaction temperature of the hydrothermal reaction is 180-260° C., the reaction time is 6-12 h, and the reaction pressure is 2.8-4.0 MPa.

[0014] Preferably, the mixed solvent with low surface tension in the fourth step is a combination of two or more of n-hexane, aliphatic hydrocarbon naphtha, n-octane, naphtha, methanol, methyl isobutyl ketone, white spirit, n-butanol, butyl acetate, cyclohexane, toluene, and o-xylene, which are mixed in any mass ratio, but the surface tension of the mixed solvent is less than 32 mN / m; the number of solvent exchanges is 2-4 times.

[0015] Preferably, in the fifth step, the low surface energy solvent-based mullite fiber-doped wet gel is placed in a fume hood for drying, and the drying is performed at room temperature and pressure for 6-12 hours; a high-temperature muffle furnace is used for sintering treatment, and the sintering treatment conditions of the high-temperature muffle furnace are: heating to 800-1000°C at a heating rate of 5-10°C / min, keeping warm for 30-60 minutes, then heating to 1500-1800°C at a heating rate of 2-5°C / min, keeping warm for 1-2 hours, and naturally cooling to room temperature; the diameter of the spinel nanorods in the mullite fiber-doped spinel nanorod aerogel is 50-100nm, and the length is 500-1500nm.

[0016] Preferably, the mullite fiber doped spinel nanorod aerogel is prepared by the above preparation method, and the density of the mullite fiber doped spinel nanorod aerogel is 0.05-0.15 g / cm 3 , temperature resistance is 1500-1800℃, thermal conductivity at 1500℃ is 0.06-0.12W / (m·K), and compression modulus is 10-30MPa.

[0017] The present invention prepares a mullite fiber reinforced spinel nanorod aerogel through the above steps, and its specific mechanism is as follows:

[0018] The formation of spinel nanorods is achieved through the coordinated mechanism of directional attachment and Ostwald ripening. First, the inorganic acid is ionized into hydrogen ions in the dispersion and uniformly adsorbed on the surface of magnesium oxide and aluminum oxide nanoparticles. Since the material has a strong solubility size dependence in the nanoscale range, the consumption of hydrogen ions by magnesium oxide and aluminum oxide nanoparticles during the growth process will eventually lead to the dissolution of smaller particles in the solution. Small magnesium oxide and aluminum oxide crystal particles will gradually gather together due to their larger curvature, higher energy and higher solubility. Based on the classic Gibbs-Curie-Wulff thermodynamic crystal growth theory, the mutually aggregated magnesium oxide and aluminum oxide nanoparticles grow into spinel nanobelt precursors with larger diameters, and then the nanobelts are split along the diameter direction during the hydrothermal reaction, and finally multiple spinel nanorod precursors with smaller diameters are obtained, and finally spinel nanorods are obtained by high-temperature calcination.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention adopts a hydrothermal synthesis method, with magnesium oxide and aluminum oxide nanoparticles as the main raw materials, and prepares spinel aerogel with nanorod morphology based on the theory of directional adsorption, Ostwald ripening and splitting model; different from the spinel nanoparticle aerogel prepared by the sol-gel method, the spinel nanorod aerogel of the present invention has a thick nano-skeleton and a low surface energy. After calcination at a temperature below the melting point of the material, sintering and fusion will not occur between the nanorods, which effectively avoids the problems of collapse of the aerogel nano-skeleton, volume shrinkage and thermal insulation failure.

[0021] (2) The present invention uses mullite nanofibers for mechanical reinforcement. On the one hand, the interface matching with the spinel nanorods is better in terms of scale. The three-dimensional interpenetrating network structure formed by the interpenetration of spinel nanorods and mullite nanofibers can effectively improve the mechanical strength of the aerogel material. On the other hand, the mullite nanofibers used in the present invention have good thermal stability and will not react with the spinel nanorods at high temperatures. At the same time, nanofiber doping can overcome the problem of aerogel density being greatly increased due to traditional micron fiber doping.

[0022] (3) The present invention adopts a normal pressure drying method to prepare the mullite fiber doped spinel nanorod aerogel, which does not require the cumbersome process flow of supercritical drying and freeze drying methods, and the process is simple and easy to achieve large-scale industrial production. That is, the water-based mullite fiber doped wet gel is solvent replaced by a low surface energy solvent, which eliminates the capillary tension difference between the inner and outer interfaces of the wet gel during the normal temperature and pressure drying process, effectively ensures the initial nanopore structure and size of the mullite fiber doped spinel nanorod aerogel, and greatly reduces the preparation cycle and production cost of the mullite fiber doped spinel nanorod aerogel material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 This is a physical picture of the mullite fiber-doped spinel nanorod aerogel in Example 1 of the present invention;

[0025] Figure 2 This is a transmission electron microscope image of the magnesium aluminum spinel nanorods in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the present invention, the present invention is further described below through examples, but these examples shall not be used to interpret the limitation of the protection scope of the present invention.

[0027] Example 1

[0028] This embodiment provides a method for preparing a mullite fiber-doped spinel nanorod aerogel, the preparation method comprising the following steps:

[0029] Step 1: Add 100 g of aluminum oxide nanoparticles (average particle size 15 nm), 100 g of magnesium oxide nanoparticles (average particle size 20 nm), and 30 g of hydrochloric acid into 3000 g of deionized water, and stir and mix them evenly at room temperature to obtain a weakly acidic dispersion with a pH of 3.8;

[0030] Step 2: After using a fully automatic fiber cutting machine to shear mullite loose wool with a fiber diameter of 500nm into mullite short fibers with a length of 500μm, 97g of the fibers are added to the weakly acidic dispersion described in the first step, and then a high-speed disperser is used to homogenize and disperse the fibers at a speed of 3000rpm for 15min to obtain a uniform and stable mullite fiber dispersion;

[0031] Step 3: placing the mullite fiber dispersion prepared in the second step in a hydrothermal reactor, and preparing a water-based mullite fiber-doped wet gel through a high-temperature and high-pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 180°C, the reaction time is 12h, and the reaction pressure is 2.8MPa;

[0032] Step 4: placing the water-based mullite fiber-doped wet gel prepared in the third step in a mixed solvent of cyclohexane / n-butanol with a mass ratio of 1:1 and performing solvent exchange three times to obtain a cyclohexane / n-butanol solvent-based mullite fiber-doped wet gel;

[0033] Step 5: placing the cyclohexane / n-butanol solvent-based mullite fiber-doped wet gel obtained in the fourth step in a fume hood, drying it at room temperature and pressure for 6 hours to obtain mullite fiber-doped aerogel, and then sintering it in a high-temperature muffle furnace to obtain mullite fiber-doped magnesium aluminum spinel nanorod aerogel; wherein the muffle furnace treatment conditions are: heating to 850°C at a heating rate of 5°C / min, keeping warm for 30 minutes, then heating to 1800°C at a heating rate of 5°C / min, keeping warm for 1 hour, and then naturally cooling to room temperature; the diameter of the magnesium aluminum spinel nanorod is 60nm and the length is 600nm.

[0034] The density of the mullite fiber-doped spinel nanorod aerogel prepared by the above steps is 0.11 g / cm 3 , temperature resistance is 1800℃, thermal conductivity at 1500℃ is 0.11W / (m·K), and compression modulus is 10MPa.

[0035] like Figure 1 Shown is a real optical picture of the mullite fiber-doped spinel nanorod aerogel in this embodiment.

[0036] like Figure 2 Shown is a transmission electron microscope image of the magnesium aluminum spinel nanorods in this example.

[0037] Example 2

[0038] This embodiment provides a method for preparing a mullite fiber-doped spinel nanorod aerogel, the preparation method comprising the following steps:

[0039] Step 1: Add 150 g of aluminum oxide nanoparticles (average particle size 15 nm), 150 g of magnesium oxide nanoparticles (average particle size 15 nm), and 50 g of sulfuric acid / hydrochloric acid (mass ratio 1:1) into 3500 g of deionized water, stir and mix evenly at room temperature to obtain a weakly acidic dispersion with a pH of 3.6;

[0040] Step 2: After using a fully automatic fiber cutting machine to cut mullite loose wool with a fiber diameter of 400nm into mullite short fibers with a length of 100μm, 200g of the fibers are added to the weakly acidic dispersion described in the first step, and then a high-speed disperser is used to homogenize and disperse the fibers at a speed of 5000rpm for 30min to obtain a uniform and stable mullite fiber dispersion;

[0041] Step 3: placing the mullite fiber dispersion prepared in the second step in a hydrothermal reactor, and preparing a water-based mullite fiber-doped wet gel through a high-temperature and high-pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 200°C, the reaction time is 10h, and the reaction pressure is 3.0MPa;

[0042] Step 4: placing the water-based mullite fiber-doped wet gel prepared in the third step in a mixed solvent of n-hexane / methyl isobutyl ketone / butyl acetate with a mass ratio of 1:1:1 for two solvent exchanges to obtain a n-hexane / methyl isobutyl ketone / butyl acetate solvent-based mullite fiber-doped wet gel;

[0043] Step 5: placing the n-hexane / methyl isobutyl ketone / butyl acetate-based mullite fiber-doped wet gel obtained in the fourth step in a fume hood, drying it at room temperature and pressure for 8 hours to obtain mullite fiber-doped aerogel, and then sintering it in a high-temperature muffle furnace to obtain mullite fiber-doped magnesium aluminum spinel nanorod aerogel; wherein the muffle furnace treatment conditions are: heating to 900°C at a heating rate of 5°C / min, keeping warm for 45 minutes, then heating to 1700°C at a heating rate of 2°C / min, keeping warm for 1 hour, and then naturally cooling to room temperature; the diameter of the magnesium aluminum spinel nanorod is 50nm and the length is 800nm.

[0044] The density of the mullite fiber-doped spinel nanorod aerogel prepared by the above steps is 0.08 g / cm 3 , temperature resistance is 1700℃, thermal conductivity at 1500℃ is 0.06W / (m·K), and compression modulus is 15MPa.

[0045] Example 3

[0046] This embodiment provides a method for preparing a mullite fiber-doped spinel nanorod aerogel, the preparation method comprising the following steps:

[0047] Step 1: Add 180 g of aluminum oxide nanoparticles (average particle size 20 nm), 180 g of magnesium oxide nanoparticles (average particle size 20 nm), and 60 g of hydrochloric acid / nitric acid (mass ratio 3:2) into 4500 g of deionized water, stir and mix evenly at room temperature to obtain a weakly acidic dispersion with a pH of 4.2;

[0048] Step 2: After using a fully automatic fiber cutting machine to cut mullite loose wool with a fiber diameter of 300nm into mullite short fibers with a length of 150μm, 280g of the fibers are added to the weakly acidic dispersion described in the first step, and then a high-speed disperser is used to homogenize and disperse the fibers at a speed of 6000rpm for 20min to obtain a uniform and stable mullite fiber dispersion;

[0049] Step 3: placing the mullite fiber dispersion prepared in the second step in a hydrothermal reactor, and preparing a water-based mullite fiber-doped wet gel through a high-temperature and high-pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 220°C, the reaction time is 7h, and the reaction pressure is 3.2MPa;

[0050] Step 4: placing the water-based mullite fiber-doped wet gel prepared in the third step in a mixed solvent of aliphatic hydrocarbon naphtha / methanol with a mass ratio of 1:2 and performing solvent exchange three times to obtain aliphatic hydrocarbon naphtha / methanol-based mullite fiber-doped wet gel;

[0051] Step 5: placing the aliphatic hydrocarbon naphtha / methanol-based mullite fiber-doped wet gel obtained in the fourth step in a fume hood, drying it at room temperature and pressure for 7.5 hours to obtain mullite fiber-doped aerogel, and then sintering it in a high-temperature muffle furnace to obtain mullite fiber-doped magnesium aluminum spinel nanorod aerogel; wherein the muffle furnace treatment conditions are: heating to 1000°C at a heating rate of 10°C / min, keeping warm for 50 minutes, then heating to 1750°C at a heating rate of 4°C / min, keeping warm for 1.5 hours, and then naturally cooling to room temperature; the diameter of the magnesium aluminum spinel nanorod is 70nm and the length is 1200nm.

[0052] The density of the mullite fiber-doped spinel nanorod aerogel prepared by the above steps is 0.10 g / cm 3 , temperature resistance is 1750℃, thermal conductivity at 1500℃ is 0.065W / (m·K), and compression modulus is 20MPa.

[0053] Example 4

[0054] This embodiment provides a method for preparing a mullite fiber-doped spinel nanorod aerogel, the preparation method comprising the following steps:

[0055] Step 1: Add 200 g of aluminum oxide nanoparticles (average particle size 8 nm), 200 g of magnesium oxide nanoparticles (average particle size 10 nm), and 100 g of hydrochloric acid / sulfuric acid / nitric acid (mass ratio 1:1:1) into 6000 g of deionized water, stir and mix evenly at room temperature to obtain a weakly acidic dispersion with a pH of 3.2;

[0056] Step 2: After using a fully automatic fiber cutting machine to cut mullite loose wool with a fiber diameter of 200nm into mullite short fibers with a length of 50μm, 500g of the fibers are added to the weakly acidic dispersion described in the first step, and then a high-speed disperser is used to homogenize and disperse the fibers at a speed of 4500rpm for 35min to obtain a uniform and stable mullite fiber dispersion;

[0057] Step 3: placing the mullite fiber dispersion prepared in the second step in a hydrothermal reactor, and preparing a water-based mullite fiber-doped wet gel through a high-temperature and high-pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 230°C, the reaction time is 8h, and the reaction pressure is 3.4MPa;

[0058] Step 4: placing the water-based mullite fiber-doped wet gel prepared in the third step in a mixed solvent of n-octane / toluene with a mass ratio of 3:2 and performing solvent exchange 4 times to obtain n-octane / toluene-based mullite fiber-doped wet gel;

[0059] Step 5: placing the n-octane / toluene-based mullite fiber-doped wet gel obtained in the fourth step in a fume hood, drying it at room temperature and pressure for 6.5 hours to obtain mullite fiber-doped aerogel, and then sintering it in a high-temperature muffle furnace to obtain mullite fiber-doped magnesium aluminum spinel nanorod aerogel; wherein the muffle furnace treatment conditions are: heating to 950°C at a heating rate of 8°C / min, keeping warm for 40 minutes, then heating to 1600°C at a heating rate of 3°C / min, keeping warm for 2 hours, and then naturally cooling to room temperature; the diameter of the magnesium aluminum spinel nanorod is 100nm and the length is 1400nm.

[0060] The density of the mullite fiber-doped spinel nanorod aerogel prepared by the above steps is 0.06 g / cm 3, temperature resistance is 1600℃, thermal conductivity at 1500℃ is 0.072W / (m·K), and compression modulus is 14MPa.

[0061] Example 5

[0062] This embodiment provides a method for preparing a mullite fiber-doped spinel nanorod aerogel, the preparation method comprising the following steps:

[0063] Step 1: Add 120 g of aluminum oxide nanoparticles (average particle size 30 nm), 120 g of magnesium oxide nanoparticles (average particle size 25 nm), and 48 g of sulfuric acid / nitric acid (mass ratio 1:2) into 3400 g of deionized water, stir and mix evenly at room temperature to obtain a weakly acidic dispersion with a pH of 4.8;

[0064] Step 2: After using a fully automatic fiber cutting machine to cut mullite loose wool with a fiber diameter of 500nm into mullite short fibers with a length of 500μm, 130g of the fibers are added to the weakly acidic dispersion described in the first step, and then a high-speed disperser is used to homogenize and disperse the fibers at a speed of 8000rpm for 15min to obtain a uniform and stable mullite fiber dispersion;

[0065] Step 3: placing the mullite fiber dispersion prepared in the second step in a hydrothermal reactor, and preparing a water-based mullite fiber-doped wet gel through a high-temperature and high-pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 250°C, the reaction time is 6.5h, and the reaction pressure is 3.8MPa;

[0066] Step 4: placing the water-based mullite fiber-doped wet gel prepared in the third step in a mixed solvent of petroleum solvent oil / butyl acetate / o-xylene with a mass ratio of 1:2:1 for three solvent exchanges to obtain a petroleum solvent oil / butyl acetate / o-xylene-based mullite fiber-doped wet gel;

[0067] Step 5: placing the petroleum solvent oil / butyl acetate / o-xylene-based mullite fiber-doped wet gel obtained in the fourth step in a fume hood, drying it at room temperature and pressure for 11 hours to obtain mullite fiber-doped aerogel, and then sintering it in a high-temperature muffle furnace to obtain mullite fiber-doped magnesium aluminum spinel nanorod aerogel; wherein the muffle furnace treatment conditions are: heating to 800°C at a heating rate of 7°C / min, keeping warm for 60 minutes, then heating to 1500°C at a heating rate of 4°C / min, keeping warm for 1 hour, and then naturally cooling to room temperature; the diameter of the magnesium aluminum spinel nanorod is 80nm and the length is 1500nm.

[0068] The density of the mullite fiber-doped spinel nanorod aerogel prepared by the above steps is 0.14 g / cm 3, temperature resistance is 1500℃, thermal conductivity at 1500℃ is 0.095W / (m·K), and compression modulus is 30MPa.

[0069] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing mullite fiber reinforced spinel nanorod aerogel, characterized in that: The following steps are involved: Aluminum oxide nanoparticles, magnesium oxide nanoparticles and inorganic acid are added to deionized water in a certain proportion, and stirred and mixed evenly at room temperature to obtain a weakly acidic dispersion; A certain amount of mullite chopped fibers is added to the weakly acidic dispersion to be homogeneously dispersed to obtain a uniform and stable mullite fiber dispersion; The mullite fiber dispersion is subjected to a high temperature and high pressure hydrothermal reaction to prepare a water-based mullite fiber-doped wet gel; placing the water-based mullite fiber-doped wet gel in a mixed solvent with low surface tension to perform solvent exchange, thereby obtaining a low surface energy solvent-based mullite fiber-doped wet gel; The low surface energy solvent-based mullite fiber-doped wet gel is dried to obtain the mullite fiber-doped aerogel, which is then sintered to obtain the mullite fiber-doped spinel nanorod aerogel.

2. The method according to claim 1, characterized in that The average particle size of the aluminum oxide nanoparticles is 8-30 nm; the average particle size of the magnesium oxide nanoparticles is 5-25 nm; the inorganic acid is any one of hydrochloric acid, sulfuric acid, and nitric acid, or a mixture of at least two of them; the mass ratio of aluminum oxide nanoparticles: magnesium oxide nanoparticles: inorganic acid: deionized water is 1:1:(0.3-0.5):(20-30); the pH value of the weakly acidic dispersion is 3-5.

3. The method according to claim 1, characterized in that The mullite chopped fibers are obtained by shearing continuous mullite loose wool, wherein the continuous mullite loose wool is mullite nanofibers with a diameter of 100-500nm; the mullite chopped fibers are sheared by a fully automatic fiber cutting machine, and the chopped fibers have a length of 50-500μm.

4. The method according to claim 1, characterized in that: The homogeneous dispersion is performed by a high-speed disperser, and the conditions for the homogeneous dispersion by the high-speed disperser are: a rotation speed of 3000-8000 rpm, a dispersion time of 15-40 min; and a concentration of the mullite fiber dispersion liquid of 3-8 wt %.

5. The method according to claim 1, characterized in that The reaction temperature of the hydrothermal reaction is 180-260° C., the reaction time is 6-12 h, and the reaction pressure is 2.8-4.0 MPa.

6. The method according to claim 1, characterized in that The low surface tension mixed solvent is a combination of two or more of n-hexane, aliphatic hydrocarbon naphtha, n-octane, naphtha, methanol, methyl isobutyl ketone, petroleum solvent oil, n-butanol, butyl acetate, cyclohexane, toluene, and o-xylene, and the surface tension of the mixed solvent is less than 32 mN / m; the number of solvent exchanges is 2-4 times.

7. The method according to claim 1, characterized in that The drying is carried out at room temperature and pressure for 6-12 hours; the sintering treatment conditions are: heating to 800-1000°C at a heating rate of 5-10°C / min, keeping warm for 30-60 minutes, then heating to 1500-1800°C at a heating rate of 2-5°C / min, keeping warm for 1-2 hours, and naturally cooling to room temperature.

8. The method according to claim 1, characterized in that The spinel nanorods in the mullite fiber-doped spinel nanorod aerogel have a diameter of 50-100 nm and a length of 500-1500 nm.

9. Mullite fiber reinforced spinel nanorod aerogel prepared according to the method of any one of claims 1 to 8.

10. The mullite fiber reinforced spinel nanorod aerogel according to claim 9, characterized in that: The density of the mullite fiber reinforced spinel nanorod aerogel is 0.05-0.15 g / cm 3 , temperature resistance is 1500-1800℃, thermal conductivity at 1500℃ is 0.06-0.12W / (m·K), and compression modulus is 10-30MPa.

Citation Information

Patent Citations

  • Method for preparing fiber-reinforced high-temperature-resistant magnesium aluminum spinel aerogel

    CN107805064A

  • High-temperature-resistant magnesium aluminate spinel aerogel and preparation method thereof

    CN118005055A